A Nexus of Stigliz’s and Islamic concepts in creating a learning society / Siti Akmar Abu Samah - Abu Samah, Siti Akmar (Faculty of Business and Management, 2015)
Even a layman will find this talk by Joseph Stigliz worth noting. The talk took place late last year, meant for fellow researchers, economists, academicians and thinkers held in Scotland on this holistic topic “Creating a Learning Society”. In finding a nexus between the thoughts of a Nobel Laureate and Islam, such a propagation has well been documented more than fourteen hundred years ago when the Quran states in Surah Al Mujadilah 58:11 that “Allah will exalt those of you who believe, and those who are given knowledge, in high degrees; and Allah is Aware of what you do”. Also, the Hadith states as narrated by Anas bin Mâlik: The Messenger of Allah said “Seeking knowledge is a duty upon every Muslim” (Sunan Ibn e Majah, Book of Sunnah, Hadith no 224, Classified as Sahih By Allama Albani). Indeed, this is a principle to adhere to for all mankind to be in the wealth of knowledge, in order to transform a society.